The Use of ICTs in the teaching of university mathematics. - Asanza Moreira, José Manuel; Huerta Cruz, Shirley; Acosta Veliz, Marjorie (Revista Universidad de Guayaquil, 2020)
ICTs are technological tools that have not only been applied to communication and research,they have been applied in all social, academic and scientific fields. As technology advancesand innovates, pedagogical techniques also change and adapt to the new needs of society forteaching, generating interest, participation and creating an appropriate environment and despitethe fact that mathematics has hardly undergone changes, its Teaching methodology has doneit, either through new dynamics, tools or methodologies,such as: applicationsfor mathematics,for augmented reality and for programming with mathematics. Through a qualitativemethodology of documentary and bibliographic review, with a synthetic analytical method, itwas determined that government support in the implementation of ICT with training programsfor teachers facilitates the adaptation and insertion of new pedagogical methodologies forteaching in the areas of college mathematics.
Keywords: ICTs; Teaching; Mathematics; University